Climate change perceptions and their individual-level determinants: A cross-European analysis. (March 2019) - Poortinga, Wouter; Whitmarsh, Lorraine; Steg, Linda; Böhm, Gisela; Fisher, Stephen
Abstract: There is now an extensive literature on the question of how individual-level factors affect climate change perceptions, showing that socio-political variables, notably values, worldviews and political orientation, are key factors alongside demographic variables. Yet little is known about cross-national differences in these effects, as most studies have been conducted in a single or small number of countries and cross-study comparisons are difficult due to different conceptualisations of key climate change dimensions. Using data from the European Social Survey Round 8 (n = 44, 387), we examine how key socio-political and demographic factors are associated with climate change perception across 22 European countries and Israel. We show that human values and political orientation are important predictors of climate change beliefs and concern, as are the demographics of gender, age, and education. Certain associations with climate change perceptions, such as the ones for the self-transcendence versus self-enhancement value dimension, political orientation, and education, are more consistent across countries than for gender and age. However, even if the direction of the associations are to a large extent consistent, the sizes of the effects are not. We demonstrate that the sizes of the effects are generally smaller in Central and Eastern European countries, and that some demographic effects are larger in Northern European as compared to Western European countries. This suggests that findings from one country do not always generalize to other national contexts.